IMPLEMENTASI SISTEM PENGAWASAN TATA TERTIB SISWA MENGGUNAKAN METODE POINT SISTEM (MPS) PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 PELAIHARI - Dwi Retnosari; Akhmad Herdian (INFO-TEKNIK, 2016)
Vocational High School (SMK) Negeri 1 Pelaihari It is one of the institutions of government agencies engaged in education. Besides the academic aspect is by scoring in each subject and the final value of the school as well as providing additional material for the evaluation of the students, SMK 1 Pelaihari also have non-academic aspects, namely by using the Surveillance System Evaluation Methods Students with Point System. In this case the school assign points for each violation and accumulated points will be used to determine the level of sanction given to students. Development of evaluation system monitoring students in the form of making application to the supervision of Code Students Method Using Point System (MPS) Based Desktop At SMK Negeri 1 Pelaihari is a system that provides information offline in the form of report data Oversight and Violation of the order made by the students with based meggunakan desktop applications Delphi 7 with MySQL database.Application Systems provide sanctions point automatically to students who violated school rules. From the accumulation of these points will be determined sanctions will be received by the students concerned in accordance with the level of sanctions specified school. Depth sanctions point applied in this school which is the first level between (25-50 points) parents / guardians of students get a call letter I, level II between (51-75 points) parents / guardians of students received a summons II, level III ( 76-90 point) parents / guardians of students received a summons III, level IV (91-99 points) parents / guardians of students received a summons IV, level V or deadline for 100 points and the rest of the parents / guardians of students received a notification letter dismissal of students. With this system so that the calculation point is no longer carried out by officers Rules of Procedure but rather automatically by the application used by the User. Users in this application are distinguished in two levels namely Officers preferably just as input data is a violation of the student and the administrator has full rights to access any menu in the app and Officers. Reports generated by the MPS student supervision system is in the form of letter to be given to students or parents informing them of the information accumulated disciplinary violations committed by students as well as the follow-up will be done to the students are.  Aplication also generate reports contains information on student enrollment, student attendance and information on the number of students quit because of the accumulation of points